Companies Act No 31 of 1909 - Kilian, Neels (UJ Press, 2019)
The 1909 Companies Act was known as the "Transvaal Act". After South Africa was established as a Union, each province had its own Companies Act. There is no indication that the 1909 Act was amended on provincial level. Later on, a new Act was written, namely the "1926 Companies Act", and it was based upon the 1909 Act. Most South African textbooks cite only the 1926 and 1973 Companies Act, without any reference to the 1909 Act. This historic legislation is however relevant to fully understand the background to South African company law. Furthermore, the 1909 Act contains more than 26 definitions, such as: a special resolution, private company, debenture, director, share and prospectus. Most of these concepts are still relevant today, 110 years later.